Synthesis of Co (II) complex of some novel 5-nitroimidazole derivatives for its antibacterial activity - D G Desai; D K Sureja; A K Seth; B R Prajapati; K I Molvi (Journal of Integrated Health Sciences)
Background: The development of resistant with the current antibiotics increases the need for discovery of more efficient drugs for the treatment of infections. Several studies have demonstrated an increase in antibacterial activity following the interaction of several compounds with metal ions. Objective: The aim of the present work was to synthesize a novel series of Cobalt (II) complexes of 2-(1- substituted-5-nitro-1H-imidazol-2-yl)-1-substitutedethanone and evaluate their in-vitro antibacterial activity. Methods: Reaction of 2-(1-substituted-5-nitro-1H-imidazol-2-yl)-1-substitutedethanone with cobalt nitrate hexahydrate under reflux condition in alkaline medium yielded metal-ligand complexes in good yield. The antibacterial activities of metal-ligand complexes were evaluated in-vitro against selected bacteria and fungi by agar well diffusion method. The zone of inhibition in mm was determined for all the ligand-metal complexes. Results: All newly synthesized metal-ligand complexes were characterized by physical and spectral analysis. Some of the investigated complexes displayed moderate inhibitory activity against gram (+)ve bacteria. None of the Co (II) complex showed inhibitory effect against gram (-)ve bacteria. Conclusion: Co (II) complexes of 2-(1-substituted-5-nitro-1H-imidazol-2-yl)-1-substitutedethanone have been synthesized and characterized. The antibacterial activity of the compounds is related to the cell wall structure of the bacteria as the results indicated that some of the tested complexes were active against gram-positive bacteria only.